Vaccination and malaria prophylaxis among Greek international travelers to Asian destinations - Androula Pavli; Chrysovalantis Silvestros; Stavros Patrinos; Helena C. Maltezou (Elsevier, 2015)
Summary: Background: International travel is rapidly increasing worldwide, and the greatest increases have occurred in tropical and subtropical areas. The aim of the survey was to investigate the pre-travel health-seeking practices of travelers to Asian destinations. Methods: A questionnaire-based survey was conducted at the Athens International Airport between the 1st of November 2011 and the 30th of April 2013. Results: A total of 1666 adult travelers participated in the study, and 69.7% were men. The mean age of the participants was 39 years. Previous travel to tropical countries was reported by 69% of the participants. The most frequent destination was the Indian subcontinent (45.0%). The main reasons for travel were visiting friends and relatives (VFRs; 36.5%) and business (32.4%). Most of the participants traveled for <1 month (51.4%). Only 24.5% pursued pre-travel consultations. Vaccinations were administered to 14.4% of the participants, and of those, 77%, 73%, and 32.5% received hepatitis A, tetanus/diphtheria, and typhoid vaccines, respectively. Malaria prophylaxis was given to 12.2% of the participants. Logistic regression analysis revealed that being male and unemployed, having an elementary level of education, traveling to visiting friends and relatives, and short durations of travel were significant determinants of not seeking pre-travel consultations. Conclusion: Significant gaps were revealed in the vaccinations and malaria prophylaxes of travelers departing to Asia. Specific educational tools should be developed to improve the awareness of travelers to high-risk destinations. Keywords: Vaccinations, Malaria, Prophylaxis, Asia, Airport, Travelers